2017
DOI: 10.1177/1045389x16682844
|View full text |Cite
|
Sign up to set email alerts
|

The field-dependent complex modulus of magnetorheological elastomers consisting of sucrose acetate isobutyrate ester

Abstract: In this work, epoxidized natural rubber-50 magnetorheological elastomer was synthesized using conventional rubber processing. The ester plasticizer sucrose acetate isobutyrate was then incorporated into epoxidized natural rubber-50 to soften the matrix and to improve the relative magnetorheological effect. The influence of sucrose acetate isobutyrate ester on the microstructures and properties of epoxidized natural rubber-50 magnetorheological elastomers were experimentally investigated. It has been identified… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
27
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
3

Relationship

4
5

Authors

Journals

citations
Cited by 38 publications
(29 citation statements)
references
References 39 publications
1
27
0
1
Order By: Relevance
“…These smart materials have been challenging researchers for many years since their development offered vast possibilities for base material selection. Among other types of MR materials such as MR fluid, MR gel, and MR grease, MR elastomers (MREs) have become a hot topic in MR research due to the high stability and compatibility between the matrix and magnetizable particles [1,2,3,4]. This fact prevents particle sedimentation and leakage issues, which frequently occur when other MR materials are utilized.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These smart materials have been challenging researchers for many years since their development offered vast possibilities for base material selection. Among other types of MR materials such as MR fluid, MR gel, and MR grease, MR elastomers (MREs) have become a hot topic in MR research due to the high stability and compatibility between the matrix and magnetizable particles [1,2,3,4]. This fact prevents particle sedimentation and leakage issues, which frequently occur when other MR materials are utilized.…”
Section: Introductionmentioning
confidence: 99%
“…This fact prevents particle sedimentation and leakage issues, which frequently occur when other MR materials are utilized. MRE has unique factors corresponding to field-dependent rheological and mechanical properties that have been investigated extensively [1,2,3,4,5,6,7,8]. In the past decade, these properties contribute to large promising applications for MREs particularly in three main areas known as: (a) vibration and noise control, (b) sensing devices, and (c) actuators [9,10,11,12,13,14,15,16,17,18].…”
Section: Introductionmentioning
confidence: 99%
“…Ubaidillah et al [92] suggested future investigations will possess ample opportunity to ameliorate the rheological properties of MRE towards device applications. In a particular example, Khairi et al [93] performed experimental work to show that MRE fabrication issues in which degraded rheological performance of MRE can be resolved by incorporating plasticizer into the matrix. Consequently, the improved properties of MRE will be validated by adopting application devices for future investigation.…”
Section: Issues Issues Issuesmentioning
confidence: 99%
“…MRs are classified as semi-active materials be-cause of only their properties were changed [1]. There are many types in MRs, including magneto-rheological fluid (MRF) that liquid phase, magneto-rheological elastomer that composite of elastomer and magnetic particle-like Waste Tire Rubber (WTR) [2] and natural rubber [3], magneto-rheological foam that foam-based and magneto-rheological gel that has a gel form.…”
Section: Introductionmentioning
confidence: 99%